2022
DOI: 10.1111/imj.15600
|View full text |Cite
|
Sign up to set email alerts
|

Preventability of venous thromboembolism in hospitalised patients

Abstract: Background Hospital‐acquired venous thromboembolism (VTE) is a major cause of morbidity and mortality. Aims To determine the proportion of patients with hospital‐acquired VTE that are preventable. Methods This was a retrospective study of patients in two tertiary care hospitals in Sydney, Australia. Data were collected for patients with hospital‐acquired VTE based on International Statistical Classification of Diseases and Related Health Problems, 10th Revision, Australian Modification (ICD‐10‐AM) coding from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…• • Process failures could occur in VTE risk assessment, prescription of appropriate VTE prevention (including mechanical prophylaxis) or the administration of prescribed VTE prophylaxis. Narayan 6 • • VTE occurring in a patient with suboptimal prophylaxis without a contraindication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• • Process failures could occur in VTE risk assessment, prescription of appropriate VTE prevention (including mechanical prophylaxis) or the administration of prescribed VTE prophylaxis. Narayan 6 • • VTE occurring in a patient with suboptimal prophylaxis without a contraindication.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported rates of potentially preventable HA-VTE of 10% to 70%. 2,5,6 The large variation in reported rates is related to the lack of a standardized definition and approach for measuring preventable HA-VTE. Missed doses of a pharmacologic agent for VTE prevention comprised the largest contributing factor for HA-VTE occurring in more than 25% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our internal data suggest each episode of HA‐VTE costs the institution approximately AU$4000–AU$7000. However, centres with higher rates of trauma and surgery would be expected to report higher rates of HA‐VTE, with only a small proportion of these considered truly preventable 4 . These events are identified through the International Classification of Diseases 10th edition (ICD‐10) coding from hospital discharge summaries, which are known to be of variable accuracy 5 .…”
Section: Figurementioning
confidence: 99%
“…However, centres with higher rates of trauma and surgery would be expected to report higher rates of HA-VTE, with only a small proportion of these considered truly preventable. 4 These events are identified through the International Classification of Diseases 10th edition (ICD-10) coding from hospital discharge summaries, which are known to be of variable accuracy. 5 Penalising institutions purely on a figure extracted from hospital coding ignores the complexity of balancing bleeding and VTE risk in this patient cohort and may discriminate against centres with high surgical caseload rather than providing an accurate representation of VTE risk assessment and prevention.…”
mentioning
confidence: 99%